Effect of lighting systems on broiler performance - Obaia, Abdel-Wahab Ramadan (Al-Mukhtar Journal of Sciences, 2011)
The present study was conducted in the Taknas, Almarg region, Libya and carried out during the period from Oktober to Abril, 2009, on broiler houses (open system). The objective of the study was to investigate the effect of lighting systems on broiler performance , and calculation of total energy consumption for broiler house. The broiler performance , include feed consumption, body weight, mortality, and production index. The production index considered as an indicator for the overall broiler performance of different lighting systems used for the study. Also, the study include , compare the conventional open system broiler house with the optimum system broiler house which the data was collected from the review of literature. The following points were concluded based on the results of this study: The 20 Watt fluorescent lamps considered the most suitable for improving bird feed consumption, bird body weight, reduce the bird’s mortality production index. The studied broiler houses, which represent by one lamp of 20 Watt fluorescent per 50 m2 and give an light intensity of 13 Lux considered as suitable for the open system broiler houses. The total energy consumption for the conventional broiler house was found to be 3866.64 kW.h/1000 bird, in comparison the selected broiler house by 1801.96 kW.h/1000, the total energy consumption was higher for the conventional system in comparison with the selected system by about 115 %.